Delayed Interval Delivery of a Second Twin after the Preterm Labor of the First One in Twin Pregnancies: Delayed Delivery in Twin Pregnancies - Yunus Aydin; Murat Celiloglu (Case Reports in Obstetrics and Gynecology)
A diamnionic dichorionic twin pregnant women (due to in vitro fertilization) admitted to emergency department at the 21st week of gestation because of regular contractions. By gynecological examination, we observed 8 cm dilated cervix with 80% effacement. Amniotic membrane was also bulging through the cervix. After evaluation delivery of the presenting fetus occurred quickly. The baby’s weight was 610 gr and no heart activity was detected. Placenta of the first fetus expulsed immediately. We decided to retain the second fetus to allow the improvement in the outcome. McDonald cerclage was performed and the patient treated with tocolytics and antibiotics, and she was continuously monitored up to the 28th week of pregnancy. After she was discharged in the 28th week, she was controlled weekly in obstetrics clinic. At the 36th gestational week which was 101 days after the cerclage procedure, 3639 g male fetus was delivered with cesarean section and had an uneventful neonatal course. Delayed-interval delivery is useful and acceptable therapeutic option for the management of the remaining fetus in twin pregnancies even after the expulsion of the placenta. Antibiotic and tocolytic administration with cervical cerclage application can be associated with longer interdelivery interval.